The Effect of Reading Prisoner Poetry on Stigma and Public Attitudes: Results from a Multigroup Survey Experiment. (January 2022) - Dum, Christopher P.; Socia, Kelly M.; George, Bengt; Neiderman, Halle M.
We examine how public attitudes toward currently/formerly incarcerated people and their reentry into society are affected by consuming information about imprisoned people. Over 1, 500 respondents from a national online survey were randomly assigned one of five sources of written information about currently and formerly incarcerated people (CFIP) (three informative pieces and two sets of incarceree poetry). They then reported their views toward them and support for reentry policies. While no differences in support for reentry initiatives across conditions were uncovered, those reading poetry with a humanizing theme applied the least amount of stigma toward currently/formerly incarcerated people.